2006
DOI: 10.1111/j.1475-1305.2006.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Range of Applicability of the Method of Caustics around Holes

Abstract: The range of applicability of the optical method of caustics, which is based on plane stress conditions, around cylindrical holes in plane specimens is investigated. The position of the generatrix curve of the caustic and the conditions, which influence its size, are defined. The dimensions of the specimen, the ratio of the thickness to the diameter of the hole, the applied stress and the dimensions of the optical set‐up influence the position of the generatrix curve of the caustic. At a critical distance from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The effort is mainly focused on the interaction of the shape of the caustics with that of the plastic zones developed around the crack tip [6, 7, 29, 33]. On the contrary, there are only limited references for the respective problem in case of perforated plates [34].…”
Section: Introductionmentioning
confidence: 99%
“…The effort is mainly focused on the interaction of the shape of the caustics with that of the plastic zones developed around the crack tip [6, 7, 29, 33]. On the contrary, there are only limited references for the respective problem in case of perforated plates [34].…”
Section: Introductionmentioning
confidence: 99%
“…al. [4] and Badalouka et al [5]. Recent work, Unger et al [6] and Hedans et al [7], has demonstrated that the method of caustics can be used to study the plasticity around the crack tip.…”
Section: Introductionmentioning
confidence: 99%
“…Also, three-dimensional wedge problems, bimaterial wedges in antiplane shear deformation and rubber wedges in large strain analysis were studied [14][15][16]. The optical method of caustics has been applied to study of the singular stress fields near holes [17,18] and in the contact problems of anisotropic materialas [19].…”
Section: Introductionmentioning
confidence: 99%